CALCULATION OF PRESSURE DROP IN NARROW ROTATING ANNULAR CLEARANCES - Nakashima, C. Y.; Oliveira Jr, S.; Caetano, E. F. (Revista de Engenharia Térmica, 2008)
This paper presents a review of correlations used for pressure drop calculation in narrow annular clearances with rotation of inner cylinder. Based on these review, a new general correlation is proposed to calculate pressure drop through such clearances. Results are compared with experimental data for different flow regimes: laminar, laminar with Taylor vortex, smooth and rough turbulent, with good agreement. The main objective is to develop a simple and general correlation that could be used for backflow calculation in twin-screw multiphase pumps. In this kind of pump, the volumetric efficiency is defined mainly by the backflow rate which occurs in the annular clearance between screw and casing. Usually, the backflow is calculated ignoring the influence of shaft rotation over pressure drop and does not consider the several possible flow regimes. Depending on operational conditions, this simplification can lead to significant errors.